A novel basic cell modeling method for elastic-viscoplastic homogenization analysis of plain-woven laminates with nesting. (October 2018) - Kubo, G.; Matsuda, T.; Sato, Y.
Highlights: A basic cell modeling method is developed for plain-woven laminates with nesting. The present method enables us to substantially reduce the analysis domain. The method achieves the modeling of a high volume fraction of fiber bundles. Elastic-viscoplastic behavior of a plain-woven laminate with nesting is predicted. The nesting affects the elastic-viscoplastic behavior of the plain-woven laminate. Abstract: In this study, a novel basic cell modeling method is developed for the elastic-viscoplastic homogenization analysis of plain-woven laminates with nesting. For this, based on the periodicity and point-symmetry of internal structures of plain-woven laminates with nesting, a hexagonal prism-shaped basic cell and its boundary conditions are proposed. The basic cell and boundary conditions are then introduced into the homogenization theory for nonlinear time-dependent composites developed by the authors. Using the present method, elastic-viscoplastic behavior of a plain-woven glass fiber-reinforced plastic (GFRP) laminate with nesting subjected to on- and off-axis loading is analyzed. In the analysis, the present method is successful in significantly reducing the analysis domain, and in achieving the modeling of a high volume fraction of fiber bundles. It is shown from the analysis results that the present method accurately predicts experimentally observed macroscopic elastic-viscoplastic behavior of the plain-woven GFRP laminate with nesting. In addition, the elastic-viscoplastic analysis of plain-woven GFRP laminates without nesting is also conducted, showing that the nesting affects elastic-viscoplastic behavior of plain-woven GFRP laminates. Graphical abstract: Image, graphical abstract